Global warming potential and economic performance of gasification-based chemical recycling and incineration pathways for residual municipal solid waste treatment in Germany. (October 2021) - Voss, Raoul; Lee, Roh Pin; Seidl, Ludwig; Keller, Florian; Fröhling, Magnus
Highlights: Assess chemical recycling for residual municipal solid waste. Comparatively evaluate chemical recycling with incineration pathways. Assess global warming potential of chemical recycling. Assess economic performance of chemical recycling. Provide data to inform regulatory and investment decisions. Abstract: Chemical recycling could facilitate the transition from a linear to a circular carbon economy, where carbon-containing waste is channeled back into the production cycle as a chemical feedstock instead of being incinerated or landfilled. However, the predominant focus on technological aspects of chemical recycling for plastic waste narrows evaluations of its potential in contributing to such a transition. Moreover, it leads to significant controversy about its role in the waste hierarchy as a possible competitor to mechanical recycling. To address these gaps in the literature, this study assesses ecological and economic impacts associated with chemical recycling of residual municipal solid waste in Germany. Combining approaches of life cycle assessment and techno-economic analysis, chemical recycling and conventional incineration-based treatment pathways are comparatively evaluated in terms of global warming potential and economic performance (i.e. fixed capital investment, net present value, dynamic payback period, and levelized cost of carbon abatement). Results indicate that compared to incineration-based conventional pathways, chemical recycling can contribute to reducing greenhouse gas emissions in low-emission energy systems. However, the economic performance of chemical recycling is highly dependent on its scale of operation. Additionally, a price premium for recycling products as well as economic instruments for penalizing CO2 emissions are identified to play important roles in the economic performance of chemical recycling.